2010
DOI: 10.1177/1934578x1000501108
|View full text |Cite
|
Sign up to set email alerts
|

New Steroidal Alkaloids from Solanum Hypomalacophyllum

Abstract: Two new steroidal alkaloids (1-2) have been isolated from the leaves and roots of Solanum hypomalacophyllum Bitter, respectively. Their structures have been elucidated as deacetoxysolaphyllidine-3-O-β-D-glucopyranoside (1) and 4-keto-5,6dihydro-(20S)-verazine (2). Furthermore, two known steroidal alkaloids, 20R-verazine and 20S-verazine, and the common secondary metabolites oleanolic acid and β-sitosterol were isolated from the roots, whereas deacetoxysolaphyllidine was obtained from the leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…These results corroborate some literature data, in which it was suggested that the addition of hydroxyl functions on a spirostane-type saponin yielded inactive compounds [18], whereas the furostane-type saponins showed cytotoxicity depending of the cell type [18]. Additionally, even if the compounds (3)(4)(5) showed antioxidant properties using ORAC assay, they do not show any potential as cellular protectants against oxidative damage of macrophage THP1. Further phytochemical and biological studies (cytotoxic, cytoprotective and antioxidant assays) on such steroidal glycosides are warranted in order to establish some structure-activity relationships.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results corroborate some literature data, in which it was suggested that the addition of hydroxyl functions on a spirostane-type saponin yielded inactive compounds [18], whereas the furostane-type saponins showed cytotoxicity depending of the cell type [18]. Additionally, even if the compounds (3)(4)(5) showed antioxidant properties using ORAC assay, they do not show any potential as cellular protectants against oxidative damage of macrophage THP1. Further phytochemical and biological studies (cytotoxic, cytoprotective and antioxidant assays) on such steroidal glycosides are warranted in order to establish some structure-activity relationships.…”
Section: Resultssupporting
confidence: 94%
“…However, no studies have been reported on S. heteracanthum. Numerous Solanum species yielded a great variety of steroidal saponins and glycoalkaloids and are of interest from both ecological and human health points of view [4]. In this paper, we will try to see chemically the existence of synonymy between these two species.…”
Section: Introductionmentioning
confidence: 98%
“…Analysis of 1 H NMR and HSQC spectra of 1 revealed signals, including three anomeric protons at δ H 5.23 (1H, br s), 4.51 (1H, d, J = 7.5 Hz), and 4.50 (1H, d, J = 7.5 Hz), an olefinic proton at δ H 5.41 (1H, br d, J = 4.5 Hz), four methyl groups at δ H 1.26 (3H, d, J = 6.5 Hz), 1.07 (3H, d, J = 6.5 Hz), 1.09 (3H, s), and 0.82 (3H, s), and other aliphatic proton signals at δ H 1.10-2.49. The appearance of two singlet methyl groups, a lot of deshielded aliphatic protons, and anomeric protons suggested compound 1 to be a steroidal alkaloid saponin [8][9][10]. The 13 C NMR spectrum of 1 contained signals corresponding to 45 carbons which were sorted by DEPT spectra into 4 non-protonated carbons, 25 methines, 4 methylenes, and 4 methyl groups.…”
mentioning
confidence: 99%
“…Thus, 10 degrees of unsaturation from molecular of 1 corresponded to one double bond, three sugar units, and a hexacyclic sterol moiety. Additionally, the presence of a nitrogen atom in compound 1 and a non-protonated carbon signal at δ C 99.9 suggested for a structure of spirosolane alkaloid, an abundant compound class in Solanum genus [8][9][10]. The assignments of methyl groups (C-21 and C-18) were then elucidated by HMBC correlations between H-21 (δ H 1.07) and C-22 (δ C 99.9)/ C-20 (δ C 43.5)/ C-17 (δ C 63.5), H-18 (δ H 0.82) and C-17.…”
mentioning
confidence: 99%
“…They are also widely used in the pharmaceutical industry to produce steroid hormones [1]. Solanum species are known as a rich source of steroidal saponins showing variable chemical diversity, such as cholestane-type, furostane-type, spirostane-type, and especially steroidal glycoalkaloids (called solanum alkaloids) [2][3][4][5][6][7]. Solanum procumbens (synonym S. hainanense) has been used in oriental medicines to treat liver diseases, such as hepatitis, cirrhosis, high level of liver enzymes [8].…”
mentioning
confidence: 99%